Characterization and quantification of in-vitro equine bone resorption in 3D using μCT and deep learning-aided feature segmentation - Grass, Debora M.; Malek, Gwladys; Taïeb, Hubert M.; Ittah, Eran; Richard, Hélène; Reznikov, Natalie; Laverty, Sheila (Bone (New York, N.Y.), 2024)
High cyclic strains induce formation of microcracks in bone, triggering targeted bone remodeling, which entails osteoclastic resorption. Racehorse bone is an ideal model for studying the effects of high-intensity loading, as it is subject to focal formation of microcracks and subsequent bone resorption. The volume of resorption in vitro is considered a direct indicator of osteoclast activity but indirect 2D measurements are used more often. Our objective was to develop an accurate, high-throughput method to quantify equine osteoclast resorption volume in μCT 3D images. Here, equine osteoclasts were cultured on equine bone slices and imaged with μCT pre- and postculture. Individual resorption events were then isolated and analyzed in 3D. Modal volume, maximum depth, and aspect ratio of resorption events were calculated. A convolutional neural network (CNN U-Net-like) was subsequently trained to identify resorption events on post-culture μCT images alone, without the need for pre-culture imaging, using archival bone slices with known resorption areas and paired CTX-I biomarker levels in culture media. 3D resorption volume measurements strongly correlated with both the CTX-I levels (p < 0.001) and area measurements (p < 0.001). Our 3D analysis shows that the shapes of resorption events form a continuous spectrum, rather than previously reported pit and trench categories. With more extensive resorption, shapes of increasing complexity appear, although simpler resorption cavity morphologies (small, rounded) remain most common, in acord with the left-hand limit paradigm. Finally, we show that 2D measurements of in vitro osteoclastic resorption are a robust and reliable proxy. •Integration of μCT and deep learning aided feature segmentation enables precise volumetric assessment of bone resorption on equine bone slices in-vitro.•The total volumes of bone resorption that were measured correlated strongly with bone resorption biomarker (CTXI) concentrations in the media.•Bone slice resorption morphology may benefit from classification along a spectrum rather than the binary categorization of pits and trenches.